Global Research Trends and Developments on Intangible Cultural Heritage: A Bibliometric Study - Rahma, Silkvi Kheir; Siti Khadijah, Ute Lies; Anwar, Rully Khairul (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study aims to provide a comprehensive overview of trends and developments in research on Intangible Cultural Heritage (ICH) using data sourced from the Scopus database. A bibliometric approach with descriptive analysis and social network mapping was employed to examine 590 articles published between 2019 and 2023. The data were processed and analyzed using VoSViewer to identify research patterns, key contributors, and thematic clusters. The findings revealed a significant annual increase in scholarly interest related to ICH. China, Spain, and the United Kingdom emerged as the top three contributing countries in terms of publication output and citation frequency. The analysis also indicates that ICH remains a complex field to preserve, influenced by modern settlement patterns that often disrupt traditional cultural practices. Furthermore, the study underscores the critical role of embracing alternative cosmologies and epistemologies in the evaluation of heritage projects, emphasizing the need to respect local cultural contexts. Co-word analysis identified "intangible cultural heritage," "cultural heritage," and "sustainability" as the dominant thematic clusters. These results suggest that future research should further explore interdisciplinary approaches to ICH, with particular attention to sustainable preservation and culturally sensitive frameworks.